Association between COVID-19 Pandemic, Blood Pressure and Pulse Rate in Young Slovak Women - Falbová, Darina; Beňuš, Radoslav; Sulis, Simona; Kolláriková, Lenka; Poliaková, Veronika; Vorobeľová, Lenka (Anthropological Review, 2025)
This study investigates the relationships between the COVID-19 pandemic, lifestyle factors, and their impact on blood pressure (BP) and pulse rate in young adult women from Slovakia. We assessed 552 adult women aged 18 to 30 years who were categorized into subgroups based on their pandemic status. The individual’s lifestyle was evaluated using a detailed questionnaire. BP and pulse rate were measured in the sitting position using a digital sphygmomanometer. Linear regression analysis tested the associations. The results showed no significant difference in physical activity and the proportion of fat mass (%) before and during the pandemic. Smoking prevalence increased during the pandemic compared to pre-pandemic levels (p = 0.152). While there were no significant differences in coffee consumption, the use of hormonal contraceptives was significantly higher during the pandemic (p = 0.021). In addition, systolic blood pressure (SBP) and pulse rate were significantly higher during the pandemic than before, indicating possible cardiovascular effects (SBP with p < 0.001 and pulse rate with p = 0.001). Regression analysis revealed that pandemic and fat mass (%) were significant predictors of SBP, while only physical activity and fat mass (%) were predictors of diastolic blood pressure (DBP). In addition, pandemic and physical activity were significant predictors of pulse rate. We observed significantly higher SBP and pulse rates during the pandemic than before in young adult women. Further studies are needed to investigate the long-term effects of the pandemic on SBP and pulse rate.